The Elementary Counsellor and Discipline - Leard, Hugh M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Elementary-school counselling- is in need of a new imag-e. It is not enough to acknowledge advances in the behavioral sciences and their implications for education. The elementary-school counsellor should have a thorough understanding of the many problem areas in which he will be involved. He should be trained to handle specific problems in a competent, effective manner. Most teachers encounter discipline problems in their classrooms. Many aspects of school functioning, teacher behavior as it pertains to classroom management, and individual psychology are related to the entire question of discipline. These are discussed and with them a number of techniques are suggested which may be used in dealing with students who display problem behavior.